THE INFLUENCE OF TALENT MANAGEMENT AND EMPLOYEE ENGAGEMENT ON EMPLOYEE RETENTION MEDIATED BY JOB SATISFACTION - Alrianti, Alvina; Ekhsan, Muhamad (Economic and Science Faculty of Islamic State University, 2024)
The purpose of this study is to determine the effect of talent management and employee engagement on employee retention with job satisfaction as mediation. The research sample was taken from electronic companies in the EJIP Cikarang Industrial Estate as many as 90 employees by saturated sample. An online survey with google form was used as a data collection tool. Data measurement uses a Likert scale. With the help of Smart PLS 3 as an analysis tool. The results show that talent management has a contribution to employee retention, while employee engagement has no contribution. Talent management and employee engagement contribute to job satisfaction. Job satisfaction contributes to employee retention and is able to contribute in mediating the influence of talent management and employee engagement on employee retention.